Peranan Proses Produksi Terhadap Optimalisasi Hasil Produksi Usaha Mikro di Kabupaten Lebak - Yumhi .; eko septian; Indra Laksana Noerwan (E-Journal Studia Manajemen, 2012)
This study aimed to examine the optimization production of micro business in Lebak. This research was conducted in the village Cibuluh Mugijaya Cigemblong Lebak using the case method. In gathering research data using interview and observation techniques. The results obtained in this study is process of making sugar greatly contribute to optimization production process of proper manner.